ANALISIS KESEJAHTERAAN RAKYAT PROVINSI BANTEN DENGAN MENGGUNAKAN METODE REGRESI LOGISTIK BINER - Megasari, Anggita; Sukmawati, Sri; Rahmatullah, Asep; Handayani, Yolla Sukma; Abdullah, Syarif (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2024)
People's welfare is the development target of every region in Indonesia. Banten Province ranks 3rd in the level of people's welfare on the island of Java. So that a factor analysis is needed to find out the influence of the people's welfare. This study aims to find out the binary logistic regression model based on factors that significantly affect the level of people's welfare in Banten Province and to find out how much the classification accuracy of the model obtained. The type of research used is quantitative research with the population of all people in Banten Province by looking at household characteristics, while the sample of 380 is secondary data from BPS Banten Province based on the results of Susenas activities with the Systematic Random Sampling technique. The results of the research obtained from this study are three factors that affect the level of people's welfare, namely the Head of Household Education factor (X3(2)) category of Junior High School Equivalent and the Head of Household Education factor (X3(3)) category of High School Equivalent and the Number of Household Members (X5(1)) category > 4 Members. The form of the binary logistic regression equation obtained is  with a model classification accuracy value of 89.7%, the classification accuracy obtained reaches > 50% which means that the binary logistic regression logit function is considered to be precise and quite good